Evaluation of the effects of mitragyna speciosa alkaloid extract on cytochrome P450 enzymes using a high throughput assay - Kong, W.M.; Chik, Z.; Ramachandra, M.; Subramaniam, U.; Aziddin, R.E.R.; Mohamed, Z. (2011)
The extract from Mitragyna speciosa has been widely used as an opium substitute, mainly due to its morphine-like pharmacological effects. This study investigated the effects of M. speciosa alkaloid extract (MSE) on human recombinant cytochrome P450 (CYP) enzyme activities using a modified Crespi method. As compared with the liquid chromatography-mass spectrometry method, this method has shown to be a fast and cost-effective way to perform CYP inhibition studies. The results indicated that MSE has the most potent inhibitory effect on CYP3A4 and CYP2D6, with apparent half-maximal inhibitory concentration (IC(50)) values of 0.78 mu g/mL and 0.636 mu g/mL, respectively. In addition, moderate inhibition was observed for CYP1A2, with an IC(50) of 39 mu g/mL, and weak inhibition was detected for CYP2C19. The IC(50) of CYP2C19 could not be determined, however, because inhibition was <50. Competitive inhibition was found for the MSE-treated CYP2D6 inhibition assay, whereas non-competitive inhibition was shown in inhibition assays using CYP3A4, CYP1A2 and CYP2C19. Quinidine (CYP2D6), ketoconazole (CYP3A4), tranylcypromine (CYP2C19) and furafylline (CYP1A2) were used as positive controls throughout the experiments. This study shows that MSE may contribute to an herb-drug interaction if administered concomitantly with drugs that are substrates for CYP3A4, CYP2D6 and CYP1A2.